2016
DOI: 10.1051/matecconf/20166600066
|View full text |Cite
|
Sign up to set email alerts
|

Key Determinants of Waste Separation Intention among Students on Campus

Abstract: Abstract. This study aims to identify the key determinants of waste separation intention among the students in Universiti Teknologi Malaysia (UTM). As reported in World Bank Report, generation of global municipal solid waste are approximately 1.3 billion tonnes per year, and it will increase approximately 2.2 billion tonnes per year by 2025. Similar trend in Malaysia which approximately eight million tonnes of municipal solid waste is produced daily. Upward trend of the solid waste generated is contributed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The result is in line with the studies by Goh et al. (2018) ; and Lee and Tanusia (2016) but contrary to the study by Ayob and Low (2016) , which found subjective norm to be insignificant to the University students’ waste separation intention which indicated that waste separation intention was not influenced by acquaintance, peer and professor. Ali and Yusof (2018) also found that SN does not have a significant relationship with BI.…”
Section: Discussionsupporting
confidence: 88%
“…The result is in line with the studies by Goh et al. (2018) ; and Lee and Tanusia (2016) but contrary to the study by Ayob and Low (2016) , which found subjective norm to be insignificant to the University students’ waste separation intention which indicated that waste separation intention was not influenced by acquaintance, peer and professor. Ali and Yusof (2018) also found that SN does not have a significant relationship with BI.…”
Section: Discussionsupporting
confidence: 88%
“…The attitude was related to behavioral intention [25]- [27]. The student who had the attitude which makes them feel good whenever they do the waste separation [28].…”
Section: Discussionmentioning
confidence: 99%
“…H2 was positively and signi cantly associated with recycling intentions. Low andAyob (2016), in terms of the intentions of university students, however, initiating a subjective norm seems to be insigni cant, as it seems to have little effect on their intentions. to separate waste.…”
mentioning
confidence: 91%